Evaluasi Kinerja Simpang Bersinyal di Simpang Empat Kedaleman Kota Cilegon - Siddiq, Rizal Nurahman; Susilowati, Susilowati (PRODI D3 TEKNIK SIPIL, 2023)
This study evaluates the operational performance of the signalised intersection at the four-way junction of Kedaleman, Cilegon City. The main objective is to assess its quality of service based on the delay times (seconds/vehicle on green) for each approach during the morning, afternoon and evening peak hours over a week. The evaluation uses a grading scale from A to F, in accordance with the Ministry of Transport Regulation No. 96 of 2015, where A indicates excellent service and F indicates poor service quality. The research methodology includes geometric surveys and the collection of daily average traffic data during peak hours for one week. The data analysis follows the guidelines of MKJI 1997 and PM 96 of 2015. The results show that the performance of the intersection averages E and F, indicating a poor level of service. In particular, on Saturday evenings, significant delays of 1104, 1106 and 1105 seconds/vehicle occur on green on all approaches, indicating a significant deterioration in performance. However, the study suggests potential improvement alternatives that could improve performance by a factor of up to 20, particularly on Saturday evenings, with potential delays of 17, 26 and 24 seconds/vehicle during green.